(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Chronic otitis media (COM) is the long-standing infection of a part or whole of middle ear cleft characterized by ear discharge and perforation. It is the commonest ear problem in adult and children. Most common presenting symptoms are ear discharge, mild to severe hearing loss, sometimes tinnitus even vertigo. Treatment of COM is mainly operative. Inactive mucosal variety of COM presents with the perforation in tympanic membrane with non-inflamed middle ear mucosa. The treatment of inactive mucosal variety of COM is Type 1tympanoplasty. It can be done by conventional temporalis fascia or cartilage graft. Both have some merits and demerits. Objective: To compare the the outcomes between reinforcement cartilage graft and temporalis fascia graft in type -1 tympanoplasty. Methods: 86 (43 patients in each group) patients with COM (inactive mucosal) who were admitted in the department of Otolaryngology – Head and Neck Surgery, Bangabandhu Sheikh Mujib Medical University, Dhaka from January 2018 to June 2019, and had fulfilled the inclusion and exclusion criteria were selected for the study. History, examinations, investigations were done. All patients underwent type 1 tympanoplasty. Prior to surgery relevant investigations were done and informed written consent was taken from all patients. In Group-A reinforcement cartilage tympanoplasty cases and in Group-B temporalis fascia tympanoplasty cases were placed. Post-operative graft uptake rate and hearing gain were compared in two groups Results: The surgical outcomes between reinforcement cartilage tympanoplasty in comparison with temporalis fascia tympanoplasty showed no significant difference of graft uptake rate and hearing gain. Conclusion: Cartilage tympanoplasty has been practised for reconstruction of perforated tympanic membrane in COM since long with variable results. Graft uptake rate in cartilage reinforcement is comparatively better than temporalis fascia graft. So, reinforcement cartilage graft can be adopted as an alternative to temporalis fascia graft in type- I tympanoplasty. Bangladesh J Otorhinolaryngol 2021; 27(2): 104-110